Application of external ear morphometry in age prediction: a pilot study - Taura, Magaji G.; Adamu, Lawan H.; Gudaji, Abdullahi; Modibbo, Musa H. (International Journal of Research in Medical Sciences, 2017)
Background: Information about age and sex that is obviously difficult to characterize can be derived from the shape of the ear which is an important but under-utilized defining feature of the head. The study aims at investigating the correlation between age and ear length, width and index for both left and right sides. The regression equation in estimation of age was formulated. Methods: A total of 219 subjects consisting of 137 males and 82 females were recruited among Bayero University students for the study. Ear length and width were measured using calibrated transparent ruler. Ear index was calculated as ear width/ ear length ×100. Pearson correlation was used to establish the relationship between age and external ear variables. The data was analysed using SPSS version 16 and P < 0.05 considered as level of significance. Results: The result shows positive higher correlation in left ear length (r= 0.24, P < 0.001) and the least was found in left ear index (r=0.002, P > 0.05). Conclusions: A linear equation model for estimation of age from given ear dimension was developed. Ear morphometry can serve as an additional tool in the estimation of age of unknown individual.